Decision-making trends in quality management: a literature review about Industry 4.0 - Lucas Schmidt Goecks; Alex Almeida dos Santos; André Luis Korzenowski (Production)
Abstract Paper aims Due to the scarcity of research on current scenarios of quality management in the 21st century, this article addresses the concepts of big data and Industry 4.0 for decision-making in quality control. Originality This article contributes to completing categorizations and answering questions that have been previously suggested. Research method This study presents a systematic literature review and qualitative data. The methodological framework shows the process of the selection and review of articles according to their alignment with the objective of the study. Main findings Seventeen articles were selected to structure the study and were classified according the categories presented in the literature. The vast majority of the research gaps pointed out in previous review have been filled since their publication. Implications for theory and practice In addition, this article presents new gaps to be filled and complements the literature and concepts about quality management and Industry 4.0.